STRATEGI PEMASARAN DAN BRANDING UMKM JAMU CAP JEMPOL DI DESA SIDOWARAS MELALUI PROGRAM KKN - Mahasiswa KKN Univeristas Lampung (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the rural economy; however, limited marketing strategies often hinder their development. This article discusses the Community Service Program (KKN) focusing on improving marketing and branding strategies for the “Jamu Cap Jempol” MSME in Sidowaras Village. This MSME is managed by a disabled entrepreneur, Sugiyani, who produces powdered herbal drinks based on customer orders. The KKN program includes creating banners, logos, and flyers to strengthen the business identity and expand its marketing reach through social media. Additionally, training on digital marketing strategies was provided to enhance product competitiveness. This study employs a qualitative approach with a descriptive-explanatory model to illustrate the changes after the program intervention. The results indicate increased community awareness of the product and improved marketing effectiveness. With better branding strategies, this MSME is expected to grow and compete in broader markets. This article is limited to the implementation of the KKN MBKM Period 1 2025 and may serve as a reference for similar programs in the future.